Enzyme-responsive polymersomes ameliorate autophagic failure in a cellular model of GM1 gangliosidosis - Paruchuri, Bipin Chakravarthy; Smith, Sarah; Larsen, Jessica (Frontiers in Chemical Engineering, 2022)
GM1 gangliosidosis is a lysosomal storage disorder caused by deficiency of β-galactosidase (βgal) and subsequent accumulation of GM1 ganglioside in lysosomes. One of the pathological aspects of GM1 gangliosidosis, and other storage disorders, is impaired autophagy, i.e., a reduced fusion of autophagosomes and lysosomes to degrade cellular waste. Enzyme replacement therapy (ERT) can effectively treat systemic deficiency but is limited by immunogenicity and shortened half-life of intravenously administered enzyme. In this paper, we report a hyaluronic acid-b-polylactic acid (HA-PLA) polymersome delivery system that can achieve an enzyme-responsive and sustained delivery of βgal to and promote the cell’s self-healing process of autophagy. HA-PLA polymersomes have an average diameter of 138.0 ± 17.6 nm and encapsulate βgal with an efficiency of 77.7 ± 3.4 %. In the presence of model enzyme Hyaluronidase, HA-PLA polymersomes demonstrate a two-fold higher release of encapsulant than without enzyme. We also identified reduced autophagy in a cellular model of GM1 Gangliosidosis (GM1SV3) compared to healthy cells, illustrated using immunofluorescence. Enhanced autophagy was reported in GM1SV3 cells treated with βgal-loaded polymersomes. Most notably, the fusion of lysosomes and autophagosomes in GM1SV3 cells returned to normal levels of healthy cells after 24 hours of polymersome treatment. The HA-PLA polymersomes described here can provide a promising delivery system to treat GM1 Gangliosidosis.